PENGGUNAAN GAME INTERAKTIF WORDWALL MATERI PESAWAT SEDERHANA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Fahma, Farisa Aina; Cahyani, Mela Eka Nuri; Romadhona, Harisma Atiqur; Yusal, Yulianti; Maiyanti, Aziza Anggi (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2024)
In this era of globalization, schools are required to be creative and innovative in implementing technology in learning so that students are active and enthusiastic in the learning process. This study aims to determine how to improve student learning outcomes after going through the learning process by using Wordwall interactive games on simple aircraft material. This study used the Classroom Action Research (PTK) method with two cycles. This research was conducted in one of the private MTs located in Kediri City. The subjects in this study were VIII A class students with a total of 18 students. The instrument used in this study is a student learning outcomes test instrument. The research instrument used is a student learning outcomes test. The results show an increase in student learning outcomes, this is indicated by an increase in the average score of cycle I and II by 21.6. In cycle I, the average score of student learning completeness reached 60.7 with 16 students below the KKM. After improvement in cycle II, the average score of completeness increased to 82 with 6 students below the KKM. The use of Wordwall interactive games on simple aircraft material can improve student learning outcomes. The use of Wordwall games is recommended as an innovative interactive learning media to improve student learning outcomes